Ruling elite, political representation and suffrage rights in the transition to democracy. Cordoba, 1890 - 1912 - Chaves, Liliana (Centro de Investigaciones de la Facultad de Filosofía y Humanidades, 2000)
The process that, initiated in 1890, led to the electoral reform of 1912 meant the passage towards a political system based on new criteria related to political representation and citizenship, which tended to inaugurate a pluralist democracy. In the provincial sphere, the ruling elite of Córdoba had to offer a response to this process. The purpose of this paper is to consider the extent to which, within the framework of the ruling elite and during this process, the demands for openness were translated into proposals for partial or substantial changes in the laws regulating the electoral system, focusing on the right of suffrage and the principle of representation. Based on them, we will try to ponder the degree of flexibility of this actor in the electoral issue, in view of the resolution of political conflicts.